Geomorphic time series reveals the constructive and destructive history of Havre caldera volcano, Kermadec arc - Spain, E.; Carey, R. J.; Whittaker, J. M.; Lucieer, V. L.; Fox, J. M.; Watson, S. J.; Tontini, F. Caratori (Frontiers in Earth Science, 2025)
Monitoring active seafloor processes requires repeated, comparable surveys to enable change detection. The change detection of the deep ocean floor, however, is rare due to a paucity of repeat data at an appropriate resolution. In this study, we use an exceptional suite of bathymetric surveys across a spatiotemporal range at the submarine Havre volcano, Kermadec arc, Southwest Pacific, to investigate geomorphic change over 13 years (2002, 2012, and 2015). The integration of bathymetric observations with remotely operated vehicle (ROV) observations and sampling data refined geomorphic boundaries, and four geomorphic groups at varying scales are interpreted: (i) large-scale tectonic and volcanic features, e.g., faults and calderas; (ii) coherent volcanic products, e.g., lavas; (iii) clastic primary volcanic products, e.g., giant pumice deposits; and (iv) mass-wasting features and products, e.g., landslide scarps. Three 25-m resolution geomorphic maps for broad-scale feature change and high-resolution 1-m autonomous underwater vehicle (AUV) bathymetry are used to develop a fine-scale geomorphic map that reveals additional landforms and processes. We integrate bathymetric data with sampling data and ROV video footage of the seafloor to refine geomorphic boundaries. We also integrate the results of previous geological studies of Havre to inform the geomorphic interpretation. Our map reveals a variety of geomorphic forms from a range of volcanic and mass-wasting processes that aid in the interpretation of the growth and evolution of submarine volcanoes. One new observation reveals a significantly larger scale of cryptodome emplacement than recognized previously recognized, accounting for an additional volume of 0.0055 km3 to the 2012 eruption products. This emplacement took place along two linear southern caldera ring faults and likely continued after the formation of the giant pumice raft on 18 July 2012. A key result is the extension of the timeline for the emplacement of volcanic products associated with the 2012 eruption, revealing an additional volume growth of 0.001 km3 on the primary dome (dome OP) between 2012 and 2015. This additional emplacement is documented in this study for the first time and extends the known volcanic emplacement timeline from 3 months to a maximum of 3 years. Our work reveals seafloor modification continuing long after an observed volcanic eruption event as lingering lava emplacement and mass wasting remobilize newly erupted and older products that comprise the edifice.